Evaluation of a Solar Photovoltaic System (SFV) to supply electrical energy to the exterior of the Central Library of the Private University of Tacna - Almanza Quispe, Williams Sergio (2025)
The generation of electricity based on the burning of natural gas is the second most predominant source in the country, emitting more than 16 million kg of CO2 per year. Achieving the transition to renewable energy sources is part of the Sustainable Development Goals to combat climate change and the use of solar energy is an alternative with great potential in Peru. For this reason, the objective of this research was to evaluate a Solar Photovoltaic System (SFV) to supply electricity to the exterior of the Central Library of the Private University of Tacna. The work consisted of estimating the energy demand to be supplied by the PVS in order to design and dimension its components, as well as to evaluate its performance under the climatic conditions of the study area. The SFV had an average daily generation of 1536.67 Wh/day, with a performance of 101% with respect to the projected demand, satisfactorily covering the needs of the student population. In addition, with the use of the SFV it was calculated that in one year the emission of 148.26 kgCO2eq/kWh would be avoided, making it a model to be implemented in other areas of the university campus to contribute to the mitigation of global warming and the fight against climate change.